2008
DOI: 10.1002/em.20407
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, dose‐range, and mutagenicity studies of methylphenidate hydrochloride in B6C3F1 mice

Abstract: Methylphenidate hydrochloride (MPH) is one of the most frequently prescribed pediatric drugs for the treatment of attention deficit hyperactivity disorder. In a recent study, increased hepatic adenomas were observed in B6C3F1 mice treated with MPH in their diet. To evaluate the reactive metabolite, ritalinic acid (RA) of MPH and its mode of action in mice, we conducted extensive investigations on the pharmacokinetics (PK) and genotoxicity of the drug in B6C3F1 mice. For the PK study, male B6C3F1 mice were gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
5
18
0
Order By: Relevance
“…Another survey on mice claimed that chronic usage of MPH can induce a significant decrease in body weight (13). Other research, on the weight of male mice of the breed B6C3F1 that received MPH chronically, demonstrated that there was a significant decrease in the weight of the treatment group compared with the control group, and a similar result was deduced for the weights of testes and seminal vesicles (11). In various research it has been shown that reduction in body weight following administration of MPH could be due to decreased appetite and lower food consumption, or reduced absorption, which is directly related to the body weight and affects animal growth (23).…”
Section: Tablesupporting
confidence: 53%
See 1 more Smart Citation
“…Another survey on mice claimed that chronic usage of MPH can induce a significant decrease in body weight (13). Other research, on the weight of male mice of the breed B6C3F1 that received MPH chronically, demonstrated that there was a significant decrease in the weight of the treatment group compared with the control group, and a similar result was deduced for the weights of testes and seminal vesicles (11). In various research it has been shown that reduction in body weight following administration of MPH could be due to decreased appetite and lower food consumption, or reduced absorption, which is directly related to the body weight and affects animal growth (23).…”
Section: Tablesupporting
confidence: 53%
“…Another study indicated that the body weight of male mice receiving MPH was significantly decreased compared to the control group (11). In another report, disorder in animal growth following long-term administration of MPH was observed (12).…”
Section: Methodsmentioning
confidence: 96%
“…It is conceivable that if such a negative selection exists, it may disproportionately remove Pig-A mutants from treated rats, obscuring a small increase in mutant frequency. With these caveats in mind, our findings are consistent with an accumulating number of negative responses for MPH in in vivo genotoxicity assays [NTP, 1995;Manjanatha et al, 2008;Witt et al, 2008;Morris et al, 2009], many of which were conducted as a result of the positive findings reported by El-Zein et al [2005]. These data also indicate that agents that reduce erythropoiesis do not necessarily elevate Pig-A RBC mutant frequencies.…”
Section: Discussionsupporting
confidence: 92%
“…Our approach of delivery in drinking water is unlimited and occurs only when the mice are awake, more closely matching human consumption patterns. The estimated maximal ingested dose with a 0.08% methylphenidate solution (B150 mg/kg/day) is much higher than that typically used in humans, although the pharmacokinetics are dramatically different between mice and humans (Manjanatha et al, 2008). Similar trends to the observed effect on circadian period were observed at lower doses, but the magnitude of effect was smaller, and the low sample size reduced statistical power.…”
Section: Discussionmentioning
confidence: 90%